373 HOMOCYSTEINE INHIBITS ENDOTHELIAL DEPENDENT VASODILATION IN HYPERTENSIVE PATIENTS WITH RENAL FAILURE BY REDUCING NITRIC OXIDE BIOAVAILABILITY. (1st January 2005) - Lorvidhaya, P.; Hassan, M.; Meyerrose, G.; Prabhakar, S. S.
Abstract : Hyperhomocysteinemia (HHCy) is recognized as an independent cardiovascular risk factor in general population and particularly in patients with chronic renal failure (CRF). However, the mechanisms by which HHCy imparts such a risk are currently unknown. We hypothesized that HHCy causes endothelial dysfunction by decreasing NO bioavailability or increasing oxidative stress or both. To examine such a hypothesis we recruited 20 subjects with hypertension and CRF (SCr > 1.5 mg/dL) and examined their endothelial dependent (post-ischemic) and endothelial independent (post-NTG or nitroglycerin) vasodilatory responses and correlated them to HHCy and CRF. The 20 control subjects had hypertension but no CRF. Diabetics and dialysis patients were excluded from the study. Total plasma homocysteine levels were measured by fluorescence polarization immunoassay. Urine and serum nitrates and nitrates (NOx) were measured using chemiluminescence technique. Hydrogen peroxide (H2 O2 ) and (peroxynitrite OONO-) were measured by spectrophotometry. Vasodilatory responses in the brachial artery were measured by high-resolution Doppler sonography by a single operator who was blinded to the patients. The results showed that the test group had higher homocysteine levels than control (17.5 ± 9.4 vs. 4.3 ± 2.4, p < .001) while the plasma NOx levels were significantly lower (8.3 ± 2.6 vs. 18.3 ± 5.7, p < .01). (table ) The test group showed increased H2 O2 and OONO- formation in addition to impairment of endothelial dependent vasodilatation (see Table above). HHCy enhanced oxidative stress and reduced NO bioavailability, thereby selectively impairing the endothelial dependent vasodilatation. These effects correlated better with HHCy than with the degree of CRF. We conclude that HHCy causes and contributes to endothelial dysfunction in hypertensive renal failure.